The phenomenon of abortion in Malaysia : religious perspectives - Wan Nadia Qistina binti Wan Zainuzzaman (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This research highlights the status of abortion according to selected religious perspectives such as Islam, Buddhism and Christianity. The selected religions consider abortion as illegal. However, they share some common conditions for abortion. The research also studies the seriousness of the phenomenon of abortion in Malaysia and several factors leading to abortion. Among the factors are the lack of religious understanding, the emergence of feminism ideology, the lack of knowledge regarding Malaysian law, accessibility to abortion pills, unwanted pregnancies and financial issues. Additionally, this research proposes some solutions to abortion in Malaysia such as to increase religious understanding through education; the role of Malaysian Ministry of Health; and the enactment of special law to restrict abortion. This research employs the qualitative method for data collection. Moreover, the data is also collected through library research including printed and electronic sources such as books, research papers, articles, journals, newspapers, websites and scriptures. Apart from that, this research also conducts textual analysis by analysing the religious scriptures of Islam, Buddhism and Christianity i.e. al-Qur'an, Ḥadīth, Sutta Pitaka and the Bible. Furthermore, the study also applies deductive method to analyse the phenomenon of abortion in Malaysia. This research is significant for Muslims, Buddhists and Christians in Malaysia to understand the status of abortion according to the respective religions and to create awareness on the phenomenon of abortion in this country.